Principals’ Instructional Leadership Strategies for Building Fostering Meaningful Learning in Primary Schools - Isvihani Abdurrahman; Enung Hasanah; Sukirman Sukirman (Institut Agama Islam Negeri (IAIN) Curup, 2026)
This study reveals the strategies employed by a primary school principal in implementing instructional leadership to foster meaningful learning. The research employed a qualitative case study with semi-structured interviews, and the data were analyzed using thematic analysis. The findings highlight three themes that reflect the principal’s instructional leadership strategies. These strategies involve supervision and management of learning resources, innovative leadership, and teacher professionalism development. These strategies reflect how principals operationalize instructional leadership to create conditions that support meaningful learning. Through systematic supervision and effective resource management, principals ensure that teaching practices are aligned with curricular goals and student needs. Their innovative leadership fosters a school culture that values creativity, reflection, and learner-centered instruction. Moreover, by facilitating teachers’ professional development, principals strengthen teachers’ capacity to design learning experiences that connect new knowledge to students’ prior understanding, an essential feature of meaningful learning as described by Ausubel’s theory.